TRANSFORMASI EKONOMI SYARIAH DI TENGAH PERUBAHAN IKLIM DAN LINGKUNGAN: STRATEGI ADAPTASI DAN MITIGASI - Sarah Salsabila Shafiyah; Fauzatul Laily Nisa (CV. KAMPUSA AKADEMIK PUBLISING, 2024)
Climate change and environmental degradation are global challenges that require collective and strategic action from various economic sectors, including the sharia economy. Sharia economics, which is based on Islamic principles, offers a unique and holistic approach to facing these challenges. Sharia economics emphasizes a balance between individual and collective interests, as well as a harmonious relationship between humans and the environment. Sustainable and ethical investment is one of the main pillars in sharia economics, where investment is directed at projects that are not only economically profitable but also socially and environmentally responsible. This article explores how sharia economic principles can be integrated into climate change adaptation and mitigation strategies. With an analytical and descriptive approach, this research highlights the role of sharia economics in achieving sustainable development and overcoming environmental challenges through the principles of justice, balance and sustainability.